Thermal, magnetic and electronic properties of non-centrosymmetric YbPt2B. (19th March 2015) - Khan, R T; Kneidinger, F; Hilscher, G; Sidorenko, A; Sologub, O; Michor, H; Bauer, E; Rogl, P; Giester, G
Abstract: Ternary YbPt2 B crystallizes in the non-centrosymmetric hexagonal CePt2 B-type structure (space group P 62 22). Electrical resistivity, specific heat and magnetic measurements reveal a magnetic instability at 5.6 K. Furthermore, a spin-reorientation of presumably a ferromagnetic type occurs around 1.5 K. The behaviour at low temperature is governed by a rather weak Kondo effect, T K ⩽ 1 K, in the presence of strong crystalline electric field splitting, with a doublet ground state. Besides, the complex magnetic behaviour presumably results from a Dzyaloshinskii–Moriya interaction triggered by the absence of inversion symmetry in the crystal structure. Scaling according to the de Gennes factor traces back magnetic ordering in YbPt2 B to the Rudermann–Kittel–Kasuya–Yoshida (RKKY) interaction and the smooth evolution of the lattice constants and the unit cell volume of REPt2 B (RE = rare earths) refers to the 4 f 13 electronic configuration of Yb in YbPt2 B.